Aggressive B-cell lymphoma: chasing the target. (30th October 2019) - Walewski, Jan
Abstract : One of the first achievements of molecular biology in lymphoma science was a discovery of cell of origin (COO) classification around 20 years ago with defining activated B-cell like (ABC) and germinal center B-cell like subtypes of diffuse large B-cell lymphoma (DLBCL) with the use of gene expression profiling. These categories were considered important as seemed to present different biology, response to treatment, and prognosis. Immunochemotherapy R-CHOP21 has been a standard of care for 2 decades, and it results in long-term disease-free survival or cure of 60% of patients with DLBCL but efficacy in an individual patient depends on age and other International Prognostic Index clinical risk factors and is within a range of 30% to more than 90%. Clinical attempts to enhance activity of immunochemotherapy in high-risk DLBCL like ABC or others included adding targeted agents to the R-CHOP backbone: bortezomib, lenalidomide, ibrutinib. Unfortunately, randomized clinical trials did not confirm the expected benefit. Recently, advanced molecular techniques were used to classify B-cell lymphomas beyond COO or MYC alterations and correlated with clinical outcome as illustrated by 2 recently published influential studies from the National Institutes of Health and from Dana Farber Cancer Center, USA. Advanced molecular pathogenesis descriptions of DLBCL provide a framework for actionable classifications that should be used for designing future clinical trials and hopefully bring success to treatment of high-risk aggressive lymphoma.